Self-Synthesizing Nanorods from Dynamic Combinatorial Libraries against Drug Resistant Cancer - Cao Yu; Yang Jian; Eichin Dominik; Zhao Fangzhe; Qi Dawei; Kahari Laura; Jia Chunman; Peurla Markus; Rosenholm Jessica M; Zhao Zhao; Jalkanen Sirpa; Li Jianwei (Wiley, 2022)
Molecular self-assembly has been widely used to develop nanocarriers for drug delivery; however, most have unsatisfactory drug loading capacity (DLC) and the dilemma between stimuli-responsiveness and stability, stagnating their translational process. Here we overcame these drawbacks using dynamic combinatorial chemistry. A carrier molecule was spontaneously and quantitatively synthesized, aided by co-self-assembly with a template molecule and an anti-cancer drug doxorubicin (DOX) from a dynamic combinatorial library that was operated by disulfide exchange under thermodynamic control. The highly selective synthesis guaranteed a stable yet pH- and redox- responsive nanocarrier with a maximized DLC of 40.1% and an enhanced drug potency to fight DOX resistance in vitro and in vivo . Our findings suggested that harnessing the interplay between synthesis and self-assembly in complex chemical systems could yield functional nanomaterials for advanced applications.